2020
DOI: 10.1111/ans.16394
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative outcomes in the elderly following colorectal cancer surgery

Abstract: Background: Despite the prevalence of colorectal cancer in the elderly, there has been a lack of recent studies examining surgical outcomes in these patients. Post-operative outcomes of colorectal cancer surgeries in those aged 80 and above will be compared to those younger than 80. Methods: A retrospective study was conducted of adults receiving surgical resections at a single tertiary centre for colorectal cancer diagnosed between January 2017 and December 2019. Patient demographics, mode of presentation, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It also was more meaningful than simply considering short-term outcomes such as 30-day mortality. 11 We found that those between 66-and 75-years had a higher OS compared to the two oldest age groups. We also found that our group of older patients had a higher rate of medical complications and on average stayed 1.5-2 days longer in hospital and had reduced OS compared to the younger patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It also was more meaningful than simply considering short-term outcomes such as 30-day mortality. 11 We found that those between 66-and 75-years had a higher OS compared to the two oldest age groups. We also found that our group of older patients had a higher rate of medical complications and on average stayed 1.5-2 days longer in hospital and had reduced OS compared to the younger patients.…”
Section: Discussionmentioning
confidence: 56%
“…We decided that it would be clinically relevant to prespecify a time period of 24 months in our comparison of these outcomes between our four categories, as many older patients from our anecdotal clinical experience found it as a useful reference time period to consider in their surgical planning and discussions. It also was more meaningful than simply considering short‐term outcomes such as 30‐day mortality 11 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have been conducted to investigate the effect of age on surgical outcomes in CRC patients. More recently, Park et al (2021) aimed to compare post-operative outcomes following CRC surgery in patients below and over 80 years of age. All patients were treated within the ERAS pathway.…”
Section: Agementioning
confidence: 99%
“…Comorbidities in subjects can increase the risk of postoperative mortality rate. 1,11 Mortality rate as a postoperative outcome is a patient's postoperative outcome based on the condition of life or death. 12 Nowadays, there have only been studies abroad that have compared the clinicopathological characteristics of early-onset and late-onset colorectal cancer (EOCRC vs LOCRC) [13][14][15] , but there is a lack of data that analyse the correlation between these clinicopathological aspects and post-operative outcomes such as mortality rates, especially in developing countries like Indonesia.…”
Section: Introductionmentioning
confidence: 99%